Setting up Service Learning Courses and Designing Syllabi - Hoffman, The Joint Education Project (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
"Service-Learning" is more than a new fad to win the popularity of students. It is a pedagogy grounded both in issues of social justice and cognitive psychology. It has been widely researched and written about. We invite you to learn more about service-learning both as an abstract practice and as a practice that has evolved at the University of Southern California.